2013
DOI: 10.5761/atcs.oa.11.01827
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iloprost on Renal Function in Patients Undergoing Coronary Artery Bypass Grafting: A Clinical Study

Abstract: Purpose: Renal dysfunction remains a serious complication of coronary artery bypass grafting (CABG) surgery and is associated with increased mortality and morbidity. To date, a number of different strategies, including new pharmacologic agents, off-pump and cardiopulmonary bypass techniques have been used to avoid it, but none of them proves the excellent result. Methods: Between April 2009 to September 2011, 185 consecutive patients with multivessel coronary artery disease undergoing elective CABG were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 28 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…These mechanisms are demonstrated with an accelerated drop in plasma creatinine in renal transplant patients . Similarly, acute renal insufficiency following cardiopulmonary bypass is attributed to hypoperfusion, as well as excessive levels of circulating cytokines . Intraoperative Iloprost administration was efficacious in maintaining creatinine levels within 25% of preoperative baseline values.…”
Section: Mechanisms Of Action and Pathophysiologymentioning
confidence: 98%
See 3 more Smart Citations
“…These mechanisms are demonstrated with an accelerated drop in plasma creatinine in renal transplant patients . Similarly, acute renal insufficiency following cardiopulmonary bypass is attributed to hypoperfusion, as well as excessive levels of circulating cytokines . Intraoperative Iloprost administration was efficacious in maintaining creatinine levels within 25% of preoperative baseline values.…”
Section: Mechanisms Of Action and Pathophysiologymentioning
confidence: 98%
“…Four were duplicate RCTs, and 5 did not occur in the setting of coronary angiography; 3 studies investigated the use of prostacyclins and calcium antagonists in cyclosporine‐induced renal failure among patients who underwent renal transplantation . One study reported protective effects of iloprost in the coronary artery bypass grafting setting . Two studies reported on iloprost and CIN and coronary angiography (Figure ) …”
Section: Study Application Of Iloprostmentioning
confidence: 99%
See 2 more Smart Citations
“…71 In patients undergoing coronary artery bypass grafting, prophylactic Iloprost administration was associated with significantly improved urine output and decreased serum creatinine. 72 Administration of Iloprost in patients with inoperable limb ischemia and kidney dysfunction (CKD stage 2) was associated with improvements in serum creatinine and eGFR. 73 Similarly, long-term administration of Beraprost in patients with diabetic CKD was shown to decrease urinary albumin excretion.…”
Section: Potential Mechanisms Of Kidney Dysfunction In Pahmentioning
confidence: 99%